Seznanjenost žensk z dejavniki tveganja za nastanek raka jajčnikov - Slana, Lea (Obzornik zdravstvene nege, 2007)
In the present paper, risk factors for ovarian cancer and the course of the disease are described. The role of a nurse in the detection, treatment and palliative care are emphasized. The results of the questionnaire on the knowledge of risk factors for ovarian cancer in the region of Ljubljana are presented. The results revealed that women are relatively well acquainted withrisk factors; however, they claim that their knowledge about this malignant disease is not sufficient. However, their familiarity with treatmentmethods is mostly general and superficial.
Keywords: ankete; Dejavniki tveganja; Health Education; Jajčnik, novotvorbe; jajčniki; Ovarian Neoplasms; Questionnaires; rak (medicina); Risk Factors; zdravstvena nega; Zdravstvena vzgoja